This I Believe - Simon, John Allsebrook Simon, Viscount (Tufts Archival Research Center, 2006)
Viscount Simon describes his belief that life is like a train which must come to an end at some point during the journey, but we should not view life with dread, even if he does not believe in an afterlife.